Sociodemographic determinants of the suicidal act in the Peruvian population: a multivariate analysis - Guevara Tirado, Alberto (2024)
Objective: To determine the sociodemographic risk factors associated with suicidal risk in the Peruvian population. Methods: An analytical and cross-sectional study was performed based on data from 24,000 violent deaths registered at the national death system (SINADEF) in 2021. Variables tested were suicidal death, other violent causes of death, sex, age group, geographic location, degree of education, and civil state. Chi-square and Cramer’s V tests were used to evaluate associations and crude and adjusted odd ratios through binary logistic regression; a p-value <0.05 and 95% confidence intervals were calculated. Results: Most of the people who died of suicide were ≤39 years old, lived on the coast, had no university degree, and had a couple at the time of death. Multivariate analysis in men identified living on the coast (OR=1.307; IC95%=1.185-1.441) and university degree (OR=1.279; IC95%=1.101-1.485) as risk factors for suicide. While in females having a couple (OR=1.311; IC95%=1.020-1.685), age ≤39 years (OR=3.516; IC905%=2.850-4.337); living on the coast (OR=1.344; IC95%=1.127-1.604) and not having a university degree (OR=1.298; IC95%=1.045-1.612) were associated with suicide. Conclusions: Geographic location and level of education in males, whereas having a couple, geographic location, age, and level of education were associated with suicide.